An aviation carbon fiber composite material for internal dispersed lightning protection and its preparation method and application

By constructing a three-dimensional conductive network in aviation carbon fiber composite materials and using four needle-shaped silver-plated zinc oxide conductive particles to increase the conductivity, the problem of easy corrosion and damage of composite materials in terms of lightning strike damage and electromagnetic wave interference is solved, and excellent lightning strike resistance is achieved. Protection and electromagnetic shielding performance.

CN116355432BActive Publication Date: 2025-01-24TONGJI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310239718.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-14
Publication Date
2025-01-24
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

Aviation carbon fiber composites have problems such as easy corrosion, easy damage, complex structure and high maintenance costs in lightning damage and electromagnetic wave interference, and the existing methods that take into account both lightning protection and electromagnetic shielding are relatively scarce.

Method used

By evenly distributing four needle-shaped silver-plated zinc oxide conductive particles between carbon fiber layers, a three-dimensional conductive network between layers is constructed to improve the conductivity of the composite material in the transverse and depth directions, thereby achieving excellent lightning protection and electromagnetic interference shielding performance.

Benefits of technology

This method significantly improves the conductivity of composite materials, enhances lightning protection and electromagnetic shielding performance, while reducing structural complexity and maintenance costs. It is light and efficient. It is suitable for the protection design of advanced composite materials aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116355432B_ABST
    Figure CN116355432B_ABST
Patent Text Reader

Abstract

The present invention relates to an aviation carbon fiber composite material for internally dispersed lightning protection, and a preparation method and application thereof. The preparation method of the composite material comprises the following steps: laying a layer of carbon fiber prepreg in a mold, and evenly spreading four-needle silver-plated zinc oxide conductive particles on the surface of the carbon fiber prepreg; laying another layer of carbon fiber prepreg on the four-needle silver-plated zinc oxide conductive particles, and evenly spreading four-needle silver-plated zinc oxide conductive particles on the surface of the carbon fiber prepreg; repeating the above steps to obtain a composite material precursor; and curing the composite material precursor by hot pressing to obtain an aviation carbon fiber composite material for internally dispersed lightning protection. Compared with the existing surface conductive lightning protection technology, the present invention has the advantages of simple structure, not easy to be damaged, and good protection effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material manufacturing, and in particular to an aviation carbon fiber composite material for internally dispersed lightning protection, and a preparation method and application thereof. Background Art

[0002] The continuous research and development of carbon fiber reinforced polymer (CFRP) composite materials with advantages such as light weight, excellent mechanical properties and strong designability has led to their large-scale use in advanced passenger aircraft such as B787 and A350, both exceeding 50%, effectively improving fuel efficiency and passenger capacity. However, compared with traditional metal materials, the low electrical conductivity of CFRP makes it extremely vulnerable to direct damage from lightning strikes (LS) and electromagnetic interference (EMI), which seriously threatens the flight safety of the aircraft and the health of the crew. Therefore, it is very necessary to design lightning protection and electromagnetic interference shielding for composite structural parts to meet airworthiness certification requirements. At present, improving the surface conductivity of composite materials to increase the conduction efficiency of lightning current and the strong reflection of electromagnetic waves is the mainstream strategy to achieve good lightning protection and electromagnetic interference shielding. Existing patents that take into account both lightning damage and electromagnetic shielding protection methods for aviation carbon fiber composite materials are relatively rare, especially at present, domestic research in this area has just started.

[0003] At present, the only inventions that take into account both lightning damage and electromagnetic shielding protection methods for aviation carbon fiber composite materials are that Fu Kunkun et al. invented an integrated aviation material for lightning protection, electromagnetic shielding and load bearing and its preparation method (CN 112706427B), J.J. Sheng et al. of Setek Technologies invented a co-cured conductive surface film for lightning and electromagnetic interference shielding of thermosetting composite materials (CN 102317383 B), A.O. Scharf of Boeing invented a method and method for manufacturing integrated lightning protection materials (CN 102006995B), and Yi Xiaosu et al. invented a lightweight lightning protection surface layer and its preparation and use methods (CN 107825810 B).

[0004] Fu Kunkun and others provide an integrated aviation material for lightning protection, electromagnetic shielding and load-bearing, including: a conductive layer and a carrier layer, wherein the carrier layer is bonded to the surface of the conductive layer by an adhesive layer, and the adhesive layer serves as an insulating layer for isolating current, the conductive layer is a nickel-plated flexible carbon fiber conductive layer, the carrier layer is a carbon fiber laminate, and the adhesive layer is a resin insulating layer. The invention also provides a method for preparing an integrated aviation material for lightning protection, electromagnetic shielding and load-bearing, including the following steps: preparing a nickel-plated flexible carbon fiber conductive layer by a chemical deposition method and preparing a carbon fiber laminate with a protection method by a hot pressing process. The present invention has the advantages of simple structure and low cost, and has no significant impact on lightning damage ( Figure 6 ) and electromagnetic interference ( Figure 7) all show excellent protective performance. At the same time, because the conductive layer matrix is ​​carbon fiber material, it shows good load-bearing capacity and has broad application prospects in aviation carbon fiber protection.

[0005] J.J. Sheng et al. prepared a resistivity less than 500 milliohms / square (such as Figure 8 ), a conductive film with a film weight of 0.01-0.15 psf (pounds per square foot) can be used on the outer surface of aircraft components to provide lightning strike protection (LSP) and electromagnetic interference (EMI) shielding. However, the invention uses silver flakes as conductive fillers, which greatly increases the cost of the aviation component protection method.

[0006] A.O. Schaff et al. have designed an integrated lightning protection method suitable for automatic laying on composite structures, which includes a paving layer composed of an organic polymer resin, a conductive layer of expanded metal foil, an isolation / adhesion layer and a carrier paper layer (such as Fig. 9 ; 22: surfacing layer; 24: conductive layer; 26: isolation or attachment layer or bonding layer; 28: carrier layer:). This protection method mainly highlights the advantages of integration and effectively solves the problems of time-consuming, high labor intensity and unstable method caused by layered laying of multi-layer methods. However, the extended metal foil is used in the conductive layer of this integrated method, which increases the weight of the protection method and then increases the weight of the aircraft, which is contrary to the goal of weight reduction.

[0007] The invention of Yi Xiaosu et al. relates to a lightweight lightning protection surface layer and its preparation and use method. The lightning protection surface layer includes a continuous conductive network, a matrix, an energy absorbing component and a conductive filler (such as Fig.10 ), the thickness of the lightning protection surface layer is 10-500μm, and the unit area mass is 20-500g / m 2 The diameter of the fiber constituting the conductive network is between 1-20μm; the particle size of the energy absorbing component is between 0.1-300μm, and its mass ratio in the resin matrix is ​​5-50%; the particle size of the conductive filler is between 10-100μm, and the content is 0-40% of the matrix mass content. This material has good flexibility and material and process compatibility, can be co-cured in different composite material curing processes, and is suitable for surface protection treatment of complex parts. However, this protection method does not mention electromagnetic wave protection and load bearing. Summary of the invention

[0008] The purpose of the present invention is to provide an aviation carbon fiber composite material with simple structure, not easy to be damaged, good protection effect and internal dispersed lightning protection, and its preparation method and application in order to address at least one of the defects of the current aviation carbon fiber structural surface conductive lightning protection system, such as easy corrosion, easy damage, complex structure and high maintenance cost. It shows excellent protection performance in terms of lightning damage and electromagnetic wave interference. At the same time, due to the four-needle spatial structure of the conductive particles, the interlayer toughness of CFRP is improved, and the load-bearing capacity outside the CFRP surface is increased, which has broad application prospects in aviation carbon fiber protection.

[0009] The purpose of the present invention can be achieved by the following technical solutions:

[0010] The inventor believes that the surface protection system is located at the outermost layer of the composite structure and is susceptible to mechanical damage. It will also cause delamination or even gas explosion when struck by lightning. If the conductive layer is vaporized or broken, the lightning current will cause serious damage to the CFRP. Through research, it was found that the in-plane conductivity of the CFRP composite material is high, while the conductivity in the depth direction is very low, only 10 -3 to 10 -2 Level 3 is the main cause of lightning damage to CFRP structural parts.

[0011] Based on this, the present invention designs an aviation carbon fiber composite material for internally dispersed lightning protection and a preparation method thereof. In this method, four-needle silver-plated zinc oxide conductive particles are evenly distributed between carbon fiber layers to replace the resin-rich area, and a three-dimensional conductive network between layers is established, which effectively improves the lateral and depth conductivity of CFRP, and at the same time achieves excellent lightning protection and electromagnetic interference shielding performance. This protection method is lightweight, efficient and practical. The specific scheme is as follows:

[0012] An aviation carbon fiber composite material for internally dispersed lightning protection, the composite material comprising carbon fiber prepregs stacked in layers, and four-needle silver-plated zinc oxide conductive particles inserted and evenly laid on the carbon fiber prepregs.

[0013] Furthermore, the surface density of the carbon fiber is 150-250g / m 2 The laying density of the four-needle silver-plated zinc oxide conductive particles on the carbon fiber is 5-25g / m 2 The overall density of the composite material is (1.50-1.70)×10 6 g / m 3 .

[0014] Furthermore, the surface density of the carbon fiber is 200g / m 2 The surface density of the four-needle silver-plated zinc oxide conductive particles on the carbon fiber is 8.89-22.22g / m 2The overall density of the composite material is (1.53-1.66)×10 6 g / m 3 .

[0015] The laying surface density is 8.89g / m 2 (0.2g), 22.22g / m 2 (0.5g). Overall density: CFRP is 1.50×10 6 g / m 3 , 0.2g Ag / T-ZnO / CFRP is 1.53×10 6 g / m 3 , 0.5g Ag / T-ZnO / CFRP is 1.66×10 6 g / m 3 .

[0016] Furthermore, the four-needle-shaped silver-plated zinc oxide conductive particles are prepared by the following method: immersing the four-needle-shaped zinc oxide in a sensitizing solution and an activating solution in sequence, washing, and drying, and then immersing it in a plating solution, and after a reduction reaction, washing and drying, obtaining the four-needle-shaped silver-plated zinc oxide conductive particles.

[0017] Tetrapod-shaped zinc oxide is an existing material and can be obtained from Hangzhou Jikang New Materials Co., Ltd. with a size of 10-50 μm.

[0018] Furthermore, the sensitizing solution comprises stannous chloride, sodium hydroxide and potassium sodium tartrate in a mass ratio of (3-10):(10-20):(10-20); the activating solution comprises palladium chloride and hydrochloric acid in a mass ratio of (0.05-0.2) g:(1-4) ml;

[0019] The plating solution includes silver nitrate and ammonia water. During the reduction reaction, the temperature of the mixed solution is increased to 30-40°C, and formaldehyde is added dropwise for 25-35 minutes. The dosage ratio of silver nitrate, ammonia water and formaldehyde is (2-8) g: (10-60) g: (8-12) ml.

[0020] The hydrochloric acid, ammonia water and formaldehyde mentioned here are all commercially available products. For example, the concentration of hydrochloric acid is about 37 wt %, the concentration of ammonia water is about 28 wt %, and the concentration of formaldehyde is about 37 wt %.

[0021] A method for preparing the above-mentioned internally dispersed lightning protection aviation carbon fiber composite material, the method comprising the following steps:

[0022] A layer of carbon fiber prepreg is spread into a mold, and four-needle-shaped silver-coated zinc oxide conductive particles are evenly spread on the surface of the carbon fiber prepreg;

[0023] Laying another layer of carbon fiber prepreg on the four-needle-shaped silver-coated zinc oxide conductive particles, and evenly spreading the four-needle-shaped silver-coated zinc oxide conductive particles on the surface of the carbon fiber prepreg;

[0024] Repeat the above steps to obtain a composite material precursor;

[0025] After the composite material precursor is cured by hot pressing, an aviation carbon fiber composite material for internally dispersed lightning strike protection is obtained.

[0026] Furthermore, when the conductive particles are dispersed, the following method is used: a metal mesh is placed on the carbon fiber prepreg, four-needle silver-plated zinc oxide conductive particles are weighed and placed on the metal mesh, and the conductive particles are evenly dispersed on the surface of the metal mesh through a metal mesh scraping process.

[0027] Furthermore, the pressure of hot pressing curing is 2-6 MPa, and the temperature rise process is: from room temperature to 120° C., then the pressure is maintained for 90 minutes, and finally reduced to room temperature.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] (1) The present invention selects zinc oxide with a four-needle spatial structure as the conductive particle skeleton, and successfully deposits metallic silver on its surface by chemical deposition method without changing its spatial structure, thereby achieving high conductivity.

[0030] (2) The present invention is an internal decentralized lightning protection system, which has the advantages of simple structure, not easy to be damaged, good protection effect, etc. compared with the surface conductive lightning protection method;

[0031] (3) The present invention selects conductive particles with a four-needle spatial structure, which can more easily construct a three-dimensional conductive network between carbon fiber layers compared to one-dimensional and two-dimensional conductive materials, thereby achieving excellent lateral and depth conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a diagram of four-needle silver-coated zinc oxide conductive particles in Example 2;

[0033] Figure 2 This is a picture of the carbon fiber laminate before lightning strike in the comparative example;

[0034] Figure 3 This is a lightning damage diagram of an unprotected carbon fiber laminate in a comparative example;

[0035] Figure 4 This is a lightning damage diagram of the carbon fiber laminate with protection method in Example 3;

[0036] Figure 5The electromagnetic shielding performance diagram of the carbon fiber laminate in Examples 2-3 and Comparative Examples;

[0037] Figure 6 A post-lightning compression performance diagram of a lightning protection, electromagnetic shielding and load-bearing integrated aviation material provided to Fu Kunkun and others;

[0038] Figure 7 Electromagnetic shielding performance diagram of a lightning protection, electromagnetic shielding and load-bearing integrated aviation material provided to Fu Kunkun and others;

[0039] Figure 8 A graph showing the resistivity of a conductive film as a function of conductive additives provided by J.J. Sheng et al.

[0040] Fig. 9 Schematic diagram of a multi-layer lightning protection material system provided to A.O. Scharf et al.

[0041] Fig.10 The diagram of lightning damage and lightning protection mechanism of composite materials provided by Yi Xiaosu et al. DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0043] An aviation carbon fiber composite material for internal dispersion lightning protection and a preparation method thereof, comprising the following steps:

[0044] Step 1: Preparation of four-needle silver-coated zinc oxide conductive particles by chemical deposition method

[0045] 1. First, add 3-10 grams of stannous chloride, 10-20 grams of sodium hydroxide and 10-20 grams of potassium sodium tartrate into 400 ml of deionized water to prepare a sensitizing solution, immerse the pre-prepared tetrapod-shaped zinc oxide into the sensitizing solution, stir magnetically at 20-40 degrees for 20-40 minutes, rinse with deionized water 3-4 times, and dry for use.

[0046] 2. Then, add 0.05-0.2 g of palladium chloride and 1-4 ml of hydrochloric acid into 500-2000 ml of deionized water to prepare an activation solution for standby use. Take 300 ml of the activation solution, immerse the sensitized tetrapod-shaped zinc oxide into the activation solution, stir magnetically at 20-40 degrees for 20-40 minutes, rinse with deionized water 3-4 times, and dry for standby use.

[0047] 3. Finally, add 2-8 grams of silver nitrate and 10-60 grams of ammonia water into 400 milliliters of deionized water, immerse the activated tetrapod-shaped zinc oxide into the plating solution, raise the temperature of the mixed solution to 30-40 degrees under magnetic stirring, add 8-12 milliliters of formaldehyde dropwise into the above plating solution, react for 30 minutes, rinse the silver-plated tetrapod-shaped zinc oxide with deionized water for 3-4 times, and dry to obtain tetrapod-shaped silver-plated zinc oxide conductive particles.

[0048] Step 2: Prepare aviation carbon fiber composite materials for internal dispersed lightning protection by metal mesh coating and hot pressing process

[0049] 1. First, a layer of carbon fiber (surface density 200g / m 2 ) prepreg is spread into the mold.

[0050] 2. Then, place the metal mesh on the prepreg, weigh a certain amount of four-needle silver-plated zinc oxide conductive particles and place them on the metal mesh, and use a metal scraper to evenly spread the conductive particles on the surface of the prepreg.

[0051] 3. Secondly, lay a layer of carbon fiber prepreg on the four-needle silver-coated zinc oxide conductive particles according to the pre-designed ply angle, and use the same metal mesh scraping process to evenly spread the silver-coated zinc oxide particles on its surface, according to [45° / 0° / -45° / 90°] s Repeat steps 2 and 3 at the plying angle to obtain a composite material precursor.

[0052] 4. The composite material precursor obtained in step 3 is subjected to a hot pressing curing method to obtain a carbon fiber composite material with an internal dispersed lightning protection system. The specific curing process is to increase the temperature from room temperature to 120°C under the condition of 2-6MPa, then continue to maintain the pressure at this temperature for 90 minutes, and finally reduce it to room temperature.

[0053] In the embodiment, the lightning protection performance of the material is tested by a lightning strike experiment, and the test standards are SAE ARP 5416 and SAE ARP 5412. Since the conductive particles in the material are intercalated between the carbon fiber prepreg layers, it does not matter which side is used for lightning strike testing.

[0054] Example 1

[0055] An aviation carbon fiber composite material for internal dispersion lightning protection and a preparation method thereof, comprising the following steps:

[0056] Step 1: Preparation of four-needle silver-coated zinc oxide conductive particles by chemical deposition method

[0057] 1. First, add 4 grams of stannous chloride, 12 grams of sodium hydroxide and 12 grams of potassium sodium tartrate into 400 ml of deionized water to prepare a sensitizing solution, immerse the pre-prepared four-needle zinc oxide into the sensitizing solution, stir magnetically at 25 degrees for 20 minutes, rinse with deionized water 3-4 times, and dry for use.

[0058] 2. Then, add 0.05 g of palladium chloride and 1 ml of hydrochloric acid into 500 ml of deionized water to prepare an activation solution for standby use. Take 300 ml of the activation solution, immerse the sensitized tetrapod-shaped zinc oxide into the activation solution, stir magnetically at 20 degrees for 20 minutes, rinse with deionized water 3-4 times, and dry for standby use.

[0059] 3. Finally, add 2 grams of silver nitrate and 10 grams of ammonia water into 400 milliliters of deionized water, immerse the activated tetrapod-shaped zinc oxide into the plating solution, raise the temperature of the mixed solution to 30 degrees under magnetic stirring, add 8 milliliters of formaldehyde dropwise into the above plating solution, react for 30 minutes, rinse the silver-plated tetrapod-shaped zinc oxide with deionized water for 3-4 times, and dry to obtain tetrapod-shaped silver-plated zinc oxide conductive particles.

[0060] Step 2: Prepare aviation carbon fiber composite materials for internal dispersed lightning protection by metal mesh coating and hot pressing process

[0061] 1. First, a layer of carbon fiber prepreg is laid into the mold.

[0062] 2. Then, place the metal mesh on the prepreg, weigh 0.1 g of four-needle silver-plated zinc oxide conductive particles and place them on the metal mesh, and evenly spread the conductive particles on the surface of the prepreg with a metal scraper.

[0063] 3. Secondly, lay a layer of carbon fiber prepreg on the four-needle silver-coated zinc oxide conductive particles according to a pre-designed laying angle, use the same metal mesh scraping process to evenly spread the silver-coated zinc oxide particles on its surface, repeat steps 2 and 3 to obtain a composite material precursor.

[0064] 4. The composite material precursor obtained in step 3 is cured by hot pressing to obtain a carbon fiber composite material with an internal dispersed lightning protection system. The specific curing process is to increase the temperature from room temperature to 120°C under 3MPa, then continue to maintain the pressure at this temperature for 90 minutes, and finally reduce it to room temperature.

[0065] Example 2

[0066] An aviation carbon fiber composite material for internal dispersion lightning protection and a preparation method thereof, comprising the following steps:

[0067] Step 1: Preparation of four-needle silver-coated zinc oxide conductive particles by chemical deposition method

[0068] 1. First, add 5 grams of stannous chloride, 14 grams of sodium hydroxide and 14 grams of potassium sodium tartrate into 400 ml of deionized water to prepare a sensitizing solution, immerse the pre-prepared four-needle zinc oxide into the sensitizing solution, stir magnetically at 30 degrees for 30 minutes, rinse with deionized water 3-4 times, and dry for use.

[0069] 2. Then, add 0.1 g of palladium chloride and 2 ml of hydrochloric acid into 1000 ml of deionized water to prepare an activation solution for standby use. Take 300 ml of the activation solution, immerse the sensitized tetrapod-shaped zinc oxide into the activation solution, stir magnetically at 30 degrees for 30 minutes, rinse with deionized water 3-4 times, and dry for standby use.

[0070] 3. Finally, add 5 grams of silver nitrate and 40 grams of ammonia water into 400 milliliters of deionized water, immerse the activated tetrapod-shaped zinc oxide into the plating solution, raise the temperature of the mixed solution to 35 degrees under magnetic stirring, add 10 milliliters of formaldehyde dropwise into the above plating solution, react for 30 minutes, rinse the silver-plated tetrapod-shaped zinc oxide with deionized water for 3-4 times, and dry to obtain tetrapod-shaped silver-plated zinc oxide conductive particles.

[0071] Step 2: Prepare aviation carbon fiber composite materials for internal dispersed lightning protection by metal mesh coating and hot pressing process

[0072] 1. First, a layer of carbon fiber prepreg is laid into the mold.

[0073] 2. Then, place the metal mesh on the prepreg, weigh 0.2g of four-needle silver-plated zinc oxide conductive particles and place them on the metal mesh, and use a metal scraper to evenly spread the conductive particles on the surface of the prepreg, so that the laying density of the conductive particles is 8.89g / m 2 .

[0074] 3. Secondly, lay a layer of carbon fiber prepreg on the four-needle silver-coated zinc oxide conductive particles according to the pre-designed laying angle, use the same metal mesh scraping process to evenly spread the silver-coated zinc oxide particles on its surface, repeat steps 2 and 3 (once for each layer, a total of 7 layers, so 7 times) to obtain a composite material precursor.

[0075] 4. The composite material precursor obtained in step 3 was cured by hot pressing to obtain a carbon fiber composite material 0.2g Ag / T-ZnO / CFRP with an internal dispersed lightning protection system, with a density of 1.53×10 6 g / m 3 The specific curing process is to increase the temperature from room temperature to 120°C under 4MPa, then continue to maintain the pressure at this temperature for 90 minutes, and finally reduce it to room temperature.

[0076] Comparative Example

[0077] The aviation carbon fiber composite material CFRP was prepared by hot pressing process with a density of 1.50×10 6 g / m 3

[0078] 1. First, follow [45° / 0° / -45° / 90°] s The carbon fiber prepreg is laid layer by layer into the mold at a laying angle to obtain a composite material precursor.

[0079] 2. The composite material precursor is cured by hot pressing to obtain an aviation carbon fiber composite material. The specific curing process is to increase the temperature from room temperature to 120°C under 4MPa, then continue to maintain the pressure at this temperature for 90 minutes, and finally reduce it to room temperature.

[0080] Figure 1 It is a four-needle zinc oxide conductive particle with silver coating on the surface. The tiny particles on the surface are redundant silver particles.

[0081] Figure 2 It can be seen that the carbon fiber composite material was intact before the lightning strike, and the surface was smooth and flat;

[0082] Figure 3 It can be seen that on the surface of the carbon fiber composite material after being struck by lightning, obvious damage such as resin pyrolysis, fiber breakage and pull-out can be seen.

[0083] Example 3

[0084] An aviation carbon fiber composite material for internal dispersion lightning protection and a preparation method thereof, comprising the following steps:

[0085] Step 1: Preparation of four-needle silver-coated zinc oxide conductive particles by chemical deposition method

[0086] 1. First, add 10 grams of stannous chloride, 20 grams of sodium hydroxide and 20 grams of potassium sodium tartrate into 400 ml of deionized water to prepare a sensitizing solution, immerse the pre-prepared four-needle zinc oxide into the sensitizing solution, stir magnetically at 35 degrees for 40 minutes, rinse with deionized water 3-4 times, and dry for use.

[0087] 2. Then, add 0.2 g of palladium chloride and 3 ml of hydrochloric acid into 2000 ml of deionized water to prepare an activation solution for standby use. Take 300 ml of the activation solution, immerse the sensitized tetrapod-shaped zinc oxide into the activation solution, stir magnetically at 35 degrees for 40 minutes, rinse with deionized water 3-4 times, and dry for standby use.

[0088] 3. Finally, add 3 grams of silver nitrate and about 40 grams of ammonia water into 400 milliliters of deionized water, immerse the activated tetrapod-shaped zinc oxide into the plating solution, raise the temperature of the mixed solution to 40 degrees under magnetic stirring, add 12 milliliters of formaldehyde dropwise into the above plating solution, react for 30 minutes, rinse the silver-plated tetrapod-shaped zinc oxide with deionized water for 3-4 times, and dry to obtain tetrapod-shaped silver-plated zinc oxide conductive particles.

[0089] Step 2: Prepare aviation carbon fiber composite materials for internal dispersed lightning protection by metal mesh coating and hot pressing process

[0090] 1. First, a layer of carbon fiber prepreg is laid into the mold.

[0091] 2. Then, place the metal mesh on the prepreg, weigh 0.5g of four-needle silver-plated zinc oxide conductive particles and place them on the metal mesh, and use a metal scraper to evenly spread the conductive particles on the surface of the prepreg, so that the laying density of the conductive particles is 22.22g / m 2 .

[0092] 3. Secondly, lay a layer of carbon fiber prepreg on the four-needle silver-coated zinc oxide conductive particles according to the pre-designed ply angle, and use the same metal mesh scraping process to evenly spread the silver-coated zinc oxide particles on its surface, according to [45° / 0° / -45° / 90°] s Repeat steps 2 and 3 at the ply laying angle (once for each layer, a total of 7 layers, so 7 times) to obtain a composite material precursor.

[0093] 4. The composite material precursor obtained in step 3 was cured by hot pressing to obtain a carbon fiber composite material Ag / T-ZnO / CFRP with an internal dispersed lightning protection system, with a density of 1.66×10 6 g / m 3 The specific curing process is to increase the temperature from room temperature to 120°C under 6MPa, then continue to maintain the pressure at this temperature for 90 minutes, and finally reduce it to room temperature.

[0094] Figure 4 It can be seen from the lightning damage of the carbon fiber composite material with 0.5g Ag / T-ZnO conductive particles added between the layers that only slight ablation occurs near the lightning injection point, but there is no obvious fiber breakage and pull-out damage.

[0095] Figure 5It can be seen that with the addition of each layer of Ag / T-ZnO conductive particles, the electromagnetic shielding performance of the carbon fiber composite material changes. When no conductive particles are added, the average electromagnetic shielding performance is only 14.53dB. When the Ag / T-ZnO content between each carbon fiber layer is 0.2, the average electromagnetic shielding performance reaches 33.06dB. When the Ag / T-ZnO content between each carbon fiber layer is 0.5, the average electromagnetic shielding performance reaches 40.99dB.

[0096] In summary, the present invention is for carbon fiber lightning protection. At present, the surface conductive lightning protection system is more widely used. However, the surface conductive lightning protection system has the problems of easy damage, complex structure and high maintenance cost. The metal mesh material also has the disadvantages of easy corrosion and low electromagnetic shielding performance. For the carbon protection method currently in the research stage, although the weight reduction effect is achieved and good lightning protection performance is also achieved, its cost is high, the preparation process is complicated and it is easy to be damaged and does not conform to practical application; and for the present invention, the silver-plated zinc oxide conductive particles with a special four-needle space structure are used to replace the resin-enriched area and intercalate between the carbon fiber layers to construct a three-dimensional conductive network, which effectively improves the depth direction and the lateral conductivity and thus gives the composite material excellent conductivity in all directions. Finally, the composite material shows excellent performance in electromagnetic shielding (EMI), lightning protection (LSP) and interlayer toughness, and can be applied to the protection design of advanced composite aircraft.

[0097] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing an aviation carbon fiber composite material for internally dispersed lightning protection, characterized in that: The composite material comprises carbon fiber prepregs stacked in layers, and four-needle-shaped silver-plated zinc oxide conductive particles inserted and evenly laid on the carbon fiber prepregs; The method comprises the following steps: (1) First, a layer of surface density of 200g / m 2 The carbon fiber prepreg is laid into the mold; (2) Then, a metal mesh was placed on the prepreg, 0.2 g of four-needle silver-plated zinc oxide conductive particles were weighed and placed on the metal mesh, and the conductive particles were evenly spread on the surface of the prepreg using a metal scraper to make the laying density of the conductive particles 8.89 g / m 2 ; (3) Secondly, a layer of carbon fiber prepreg is laid on the four-needle silver-coated zinc oxide conductive particles according to a pre-designed laying angle, and the silver-coated zinc oxide particles are evenly spread on the surface using the same metal mesh coating process, and steps (2) and (3) are repeated to obtain a composite material precursor; (4) The composite material precursor obtained in step (3) is subjected to a hot pressing curing method to obtain a carbon fiber composite material 0.2g Ag / T-ZnO / CFRP with an internal dispersed lightning protection system, with a density of 1.53×10 6 g / m 3 The specific curing process is to increase the temperature from room temperature to 120°C under 4MPa, then continue to maintain the pressure at this temperature for 90 minutes, and finally reduce it to room temperature.

2. The method for preparing an aviation carbon fiber composite material for internally dispersed lightning protection according to claim 1, characterized in that: The four-needle silver-plated zinc oxide conductive particles are prepared by the following method: the four-needle zinc oxide is immersed in a sensitizing solution and an activating solution in sequence, washed, and dried, and then immersed in a plating solution, and after a reduction reaction, washed and dried to obtain the four-needle silver-plated zinc oxide conductive particles.

3. The method for preparing an aviation carbon fiber composite material for internally dispersed lightning protection according to claim 2, characterized in that: The sensitizing solution comprises stannous chloride, sodium hydroxide and potassium sodium tartrate in a mass ratio of (3-10):(10-20):(10-20); the activating solution comprises palladium chloride and hydrochloric acid in a mass ratio of (0.05-0.2) g:(1-4) ml.

4. The method for preparing an aviation carbon fiber composite material for internally dispersed lightning protection according to claim 2, characterized in that: The plating solution includes silver nitrate and ammonia water. During the reduction reaction, the temperature of the mixed solution is increased to 30-40°C, and formaldehyde is added dropwise for 25-35 minutes. The dosage ratio of silver nitrate, ammonia water and formaldehyde is (2-8) g: (10-60) g: (8-12) ml.

5. An application of an aviation carbon fiber composite material for internally dispersed lightning protection prepared by the preparation method according to claim 1, characterized in that: The composite material is used in a surface conductive lightning protection system.

Citation Information

Patent Citations

  • System and method for fabrication of integrated lightning strike protection material

    CN102006995B

  • Co-curable, conductive surfacing films for lightning strike and electromagnetic interference shielding of thermoset composite materials

    CN102317383B

  • A lightweight lightning protection surface layer and its preparation and application method

    CN107825810B

  • Integrated aerospace materials for lightning protection, electromagnetic shielding, and load bearing, and their preparation methods

    CN112706427B

  • Method for promoting conductivity of carbon fiber laminated composites by using conductive inorganic whiskers

    CN102838763A